A semi-rebonded magnesia-chrome brick for copper smelting furnace and its preparation method
By adding aluminum nitride, nickel oxide and chromium oxide to magnesium chromium bricks, magnesium aluminum oxynitride and magnesium chromium spinel are used, and the slag resistance and high-temperature strength of magnesium chromium bricks are solved. The problem has improved the performance of the copper smelting furnace and reduced environmental pollution.
Patent Information
- Application Number
- CN202411355547.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The slag resistance and high-temperature strength properties of magnesium-chromium bricks in copper smelting furnaces are insufficient, and chromium elements may form toxic compounds at high temperatures, causing harm to the environment and organisms.
Magnesium-chromium sand, electromelted magnesium sand and chromium ore are used as the main raw materials, aluminum nitride, nickel oxide and chromium oxide are added, and magnesium-aluminum-oxynitride and magnesium-chromium spinel are generated through co-milling and sintering technology to improve slag resistance and high temperature Performance and enhance binding strength and prevent chromium oxidation through the combination of resin powder and citric acid.
The slag resistance, thermal shock stability and high temperature strength of magnesium-chrome bricks used in copper smelting furnaces have been significantly improved, and the risk of pollution to the environment has been reduced.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a semi-recombined magnesia-chrome brick for a copper smelting furnace and a preparation method thereof. Background Art
[0002] Nonferrous metals are widely used and come in many varieties. The five most commonly used nonferrous metals are copper, aluminum, lead, zinc and nickel. There are many different smelting methods for nonferrous metallurgy, and there are many types of kilns, which can generally be divided into three categories: smelting furnaces, refining furnaces and casting furnaces, each of which is divided into several types. The copper and nickel converters consume the most refractory materials in nonferrous smelting. The copper converter has a short lining life and high labor intensity, which has become a weak link in the copper smelting production process. In copper smelting production, slag erosion and matte penetration are one of the main factors causing refractory damage. The lining of the copper converter is mostly made of magnesia-chrome bricks, which have good resistance to rapid cooling and heating, good wear resistance, and good resistance to alkaline slag erosion.
[0003] The raw materials for preparing magnesia-chrome bricks are mainly magnesia sand, chrome ore, magnesia-chrome sand, etc. The Chinese patent document with publication number CN103332940B discloses a semi-recombined magnesia-chrome brick, which is made of fused magnesia-chrome synthetic material, high-purity magnesia sand, chrome concentrate, sintered magnesia-chrome synthetic material, Cr2O3 ultrafine powder, metal admixtures, additives, and binders. By adding metal powder and salt leaching process, the porosity in the bricks is reduced, a microporous structure is formed, and the thermal shock stability is improved. At the same time, the brick has high density, low porosity, high temperature strength, excellent thermal shock resistance and slag erosion resistance. However, chromium ore usually contains a certain proportion of aluminum oxide, which can react with slag, resulting in poor slag resistance of the furnace lining, causing the furnace lining to be corroded and penetrated by ferrosilicate slag, affecting the service life of the furnace lining, and the high temperature strength performance of magnesia-chrome bricks still needs to be improved. In addition, the chromium element in magnesia-chrome bricks may form toxic chromium-containing compounds (such as These compounds are seriously harmful to the environment and organisms. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a semi-recombined magnesia-chrome brick for a copper smelting furnace and a preparation method thereof, which has good slag resistance, high temperature strength and thermal shock stability under the copper smelting working environment.
[0005] In order to solve the above problems, the first aspect of the present invention provides a semi-rebonded magnesia-chrome brick for a copper smelting furnace, wherein the raw materials for preparing the semi-rebonded magnesia-chrome brick include the following components in mass percentage:
[0006] Magnesia-chrome sand 3%~18%, magnesia-chrome low-iron sand 52%~70%, fused magnesia sand 5%~15%, baltichrome concentrate 5%~15%, baltichrome lump 0.5%~5%, aluminum nitride 0.5%~6%, nickel oxide 0.1%~1%, chromium oxide 0.1%~4%, resin powder 0~0.8%, citric acid 0~2.7%; added dextrin 1%~5%, water 0.5%~2.5%; the mass percentage of resin powder and citric acid is not 0.
[0007] Preferably, the raw materials for its preparation include the following components in percentage by mass:
[0008] Magnesia-chrome sand 5%~15%, magnesia-chrome low-iron sand 55%~67%, fused magnesia sand 7%~13%, baltichrome concentrate 9%~13%, baltichrome lump 1%~4%, aluminum nitride 1%~5%, nickel oxide 0.1%~0.6%, chromium oxide 0.5%~3%, resin powder 0~0.5%, citric acid 0~2%; added dextrin 1%~4%, water 1%~2%; the mass percentage of resin powder is not 0.
[0009] Preferably, the raw materials for its preparation include the following components in percentage by mass:
[0010] Magnesia-chrome sand 5%~10%, magnesia-chrome low-iron sand 60%~65%, fused magnesia sand 8%~12%, baltichrome concentrate 10.4%~12%, baltichrome lump 2%~3%, aluminum nitride 2%~3%, nickel oxide 0.3%~0.6%, chromium oxide 1%~1.5%, resin powder 0.2%~0.3%, citric acid 0.5%~1.2%; added dextrin 2%~3%, water 1.4%; the mass percentage of resin powder is not 0.
[0011] Preferably, in the chrome concentrate and chrome lump, Cr2O3≥56wt%, Fe2O3≤15wt%, MgO≤14wt%, Al2O3≤11wt%, SiO2≤1.5wt%, CaO≤0.59 wt%;
[0012] In the magnesia-chrome sand, MgO≥48wt%, Cr2O3≥30wt%, Fe2O3≤12wt%, Al2O3≤6.8wt%, CaO≤1.3 wt%, and SiO2≤1.2wt%.
[0013] In the magnesium-chromium low-iron sand, MgO≥76wt%, Cr2O3≥20.43wt%, Fe2O3≤9.13wt%, Al2O3≤5.34wt%, CaO≤1.36wt%, and SiO2≤0.81wt%.
[0014] In the fused magnesia, MgO≥97.21wt%, CaO≤1.13wt%, SiO2≤0.84wt%, Fe2O3≤0.59wt%, and Al2O3≤0.17wt%.
[0015] Preferably, the mass ratio of chrome concentrate to aluminum nitride is 1.9-9.2:1.
[0016] Preferably, the mass ratio of the total mass of the balboa chrome concentrate and the balboa chrome lump to nickel oxide is 22-66:1.
[0017] Preferably, the mass ratio of the total mass of the balboa chrome concentrate and the balboa chrome lump to chromium oxide is 4.2-26.4:1.
[0018] Preferably, the magnesia-chrome sand includes magnesia-chrome sand with a particle size of >3mm and ≤5mm, magnesia-chrome sand with a particle size of >1mm and ≤3mm, magnesia-chrome sand with a particle size of >0mm and ≤1mm, and magnesia-chrome sand with a particle size of 200 mesh; the mass ratio of magnesia-chrome sand with a particle size of >3mm and ≤5mm, magnesia-chrome sand with a particle size of >1mm and ≤3mm, magnesia-chrome sand with a particle size of >0mm and ≤1mm, and magnesia-chrome sand with a particle size of 200 mesh is 2~3:4~6:4~5:1;
[0019] The magnesium-chromium low-iron sand includes magnesium-chromium low-iron sand with a particle size of >3mm and ≤5mm, magnesium-chromium low-iron sand with a particle size of >1mm and ≤3mm, and magnesium-chromium low-iron sand with a particle size of >0mm and ≤1mm; the mass ratio of magnesium-chromium low-iron sand with a particle size of >3mm and ≤5mm, magnesium-chromium low-iron sand with a particle size of >1mm and ≤3mm, and magnesium-chromium low-iron sand with a particle size of >0mm and ≤1mm is 0~1:0~1:0~1;
[0020] The particle size of the balchrome concentrate is 200 mesh; the particle size of the balchrome lump ore is greater than 0 mm and less than or equal to 5 mm;
[0021] The particle size of the fused magnesia is 200 meshes.
[0022] The second aspect of the present invention provides a method for preparing the semi-rebonded magnesia-chrome brick for a copper smelting furnace, comprising the following steps:
[0023] S1. The aluminum nitride, chrome concentrate, fused magnesia are mixed and co-grinded to obtain a co-grinded powder;
[0024] S2. The co-ground powder is mixed with magnesia-chrome sand, magnesia-chrome low-iron sand, Pakistani chrome lump ore, nickel oxide, chromium oxide, and resin powder to obtain an initial mixture;
[0025] S3. Add dextrin and water to the initial mixture and mix to obtain a mixture;
[0026] S4. forming and firing the mixture to obtain the semi-rebonded magnesia-chrome brick for the copper smelting furnace.
[0027] Preferably, the firing specifically includes the following steps: firing the formed mixture in a firing kiln, the firing temperature is 1800-1820°C, the pushing speed is 120 minutes per car, and the firing section is kept warm for 6 hours; there must be no pulp-combined products in the first 8 cars and the last 8 cars in the firing kiln.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The semi-recombined magnesia-chrome brick for a copper smelting furnace of the present invention uses magnesia-chrome sand, fused magnesia sand and chrome ore as main raw materials, and aluminum nitride is added. Since the chrome ore contains a certain amount of aluminum oxide, the aluminum oxide will react with the slag in the copper smelting furnace at the working environment temperature, resulting in poor slag resistance of the copper smelting furnace. At the firing temperature, the aluminum nitride can react with magnesium oxide and the aluminum oxide in the chrome ore to generate stable magnesium aluminum oxide nitride (MgAlON). Since the magnesium aluminum oxide nitride crystal phase is stable and will not react with the slag in the copper smelting furnace at the working temperature, the aluminum oxide in the brick can be fixed, thereby improving the slag resistance of the copper smelting furnace.
[0030] At the working temperature, magnesium and chromium in magnesia-chrome sand, magnesia sand and chrome ore can react to form magnesia-chrome spinel or magnesia-chrome solid solution. The two raw materials can be effectively combined by reaction sintering, and the bonding strength is high. Magnesia-chrome bricks have good high-temperature performance. However, the reaction of magnesium and chromium in magnesia-chrome sand, magnesia sand and chrome ore usually has a low conversion rate, incomplete reaction and low degree of bonding of raw materials. The semi-recombined magnesia-chrome brick for copper smelting furnace of the present invention adds nickel oxide. Nickel oxide and iron oxide in chrome ore can generate nickel-iron spinel at the firing temperature, which is in liquid phase at high temperature. The liquid phase can promote the conversion of magnesium-chrome sand, magnesia sand and chrome ore. The reaction of magnesium and chromium promotes the formation of magnesia-chrome spinel, greatly improves the binding property of raw materials, and improves the high-temperature performance of magnesia-chrome bricks. The present invention also adds chromium oxide, which has a higher purity than chromium ore, and reacts more completely with magnesia-chrome sand and magnesia sand to generate more magnesia-chrome spinel. The chromium oxide is a micro powder, which can fill pores and improve the strength of magnesia-chrome bricks. However, chromium oxide is expensive. The higher the amount of chromium oxide added, the higher the strength of the magnesia-chrome brick and the higher the price. However, the thermal shock stability is reduced, molding is difficult, and layer cracking is easy to occur. The addition of an appropriate amount of chromium oxide can improve the comprehensive performance of magnesia-chrome bricks.
[0031] During the firing process, the formation of magnesia-chrome spinel and magnesia-aluminum-oxygen-nitrogen phase will produce a certain amount of volume expansion. The present invention adds resin powder, which itself cooperates with dextrin to improve the bonding strength of magnesia-chrome bricks at different temperatures. The resin powder is mainly used to improve the bonding strength of magnesia-chrome bricks at 200°C. In addition, more importantly, as the temperature rises, the carbon in the resin powder disappears and produces holes, which is convenient for the growth of the above-mentioned crystal phase and prevents the magnesia-chrome brick from excessive expansion and cracking. Due to the presence of trivalent chromium in magnesia-chrome bricks, it is easily oxidized to generate hexavalent chromium during use, which has certain toxicity and affects the environment. The present invention adds citric acid, which can reduce the hexavalent chromium generated in the brick to trivalent chromium. At the same time, the resin powder can also generate a reducing atmosphere inside the brick, and as the temperature rises, it prevents the trivalent chromium from being converted to hexavalent chromium. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The first aspect of the present invention provides a semi-rebonded magnesia-chrome brick for a copper smelting furnace, wherein the raw materials for preparing the semi-rebonded magnesia-chrome brick include the following components in percentage by mass:
[0034] Magnesia-chrome sand 3%~18%, magnesia-chrome low-iron sand 52%~70%, fused magnesia sand 5%~15%, baltichrome concentrate 5%~15%, baltichrome lump 0.5%~5%, aluminum nitride 0.5%~6%, nickel oxide 0.1%~1%, chromium oxide 0.1%~4%, resin powder 0~0.8%, citric acid 0~2.7%; added dextrin 1%~5%, water 0.5%~2.5%; the mass percentage of resin powder and citric acid is not 0.
[0035] The semi-recombined magnesia-chrome brick for copper smelting furnace of the present invention uses magnesia-chrome sand, fused magnesia sand and chrome ore as main raw materials, and aluminum nitride is added. Since chrome ore contains a certain amount of aluminum oxide, aluminum oxide will react with slag in the copper smelting furnace at the working environment temperature, resulting in poor slag resistance of the copper smelting furnace. At the firing temperature, aluminum nitride can react with magnesium oxide and aluminum oxide in the chrome ore to generate stable magnesium aluminum oxide nitrogen (MgAlON). Since the crystal phase of magnesium aluminum oxide nitrogen is stable, it will not react with slag in the copper smelting furnace at the working temperature, so the aluminum oxide in the brick can be fixed, thereby improving the slag resistance of the copper smelting furnace. Furthermore, at the working temperature, the aluminum oxide in the magnesia-chrome sand, magnesia sand and chrome ore will react with the slag in the copper smelting furnace. Magnesium and chromium can react to form magnesia-chrome spinel or magnesia-chrome solid solution. Through reaction sintering, the two raw materials can be effectively combined together with high bonding strength. Magnesia-chrome bricks have good high-temperature performance. However, the reaction of magnesium and chromium in magnesia-chrome sand, magnesia sand and chrome ore usually has a low conversion rate, incomplete reaction and low degree of bonding of raw materials. The semi-recombined magnesia-chrome bricks for copper smelting furnaces of the present invention add nickel oxide. Nickel oxide and iron oxide in chromium ore can form nickel-iron spinel at the firing temperature, which is in liquid phase at high temperature. The liquid phase can promote the reaction of magnesium and chromium in magnesia-chrome sand, magnesia sand and chrome ore, promote the formation of magnesia-chrome spinel, greatly improve the bonding of raw materials, and improve the performance of magnesia-chrome bricks. High temperature performance, the present invention also adds chromium oxide, chromium oxide has higher purity than chrome ore, and its reaction with magnesia-chrome sand and magnesia sand is more complete, and more magnesia-chrome spinel can be generated. The chromium oxide is a micro powder, which can fill pores and improve the strength of magnesia-chrome bricks, but chromium oxide is expensive. The higher the amount of chromium oxide added, the higher the strength of magnesia-chrome bricks, the higher the price, but the thermal shock stability is reduced, the molding is difficult, and it is easy to produce layer cracking. The addition of an appropriate amount of chromium oxide can improve the comprehensive performance of magnesia-chrome bricks; during the firing process, the generation of magnesia-chrome spinel and magnesia-aluminum oxygen-nitrogen phase will produce a certain amount of volume expansion. The present invention adds resin powder, which itself acts as a paste The resin powder and the resin powder cooperate with each other to improve the bonding strength of the magnesia-chrome brick at different temperatures. The resin powder is mainly used to improve the bonding strength of the magnesia-chrome brick at 200°C. In addition, more importantly, as the temperature rises, the carbon in the resin powder disappears and generates holes, which is convenient for the growth of the above-mentioned crystal phase and prevents the magnesia-chrome brick from excessive expansion and cracking. Due to the presence of trivalent chromium in the magnesia-chrome brick, it is easily oxidized to generate hexavalent chromium during use, which has certain toxicity and affects the environment. Citric acid is added to the present invention to reduce the hexavalent chromium generated in the brick to trivalent chromium. At the same time, the resin powder can also generate a reducing atmosphere inside the brick to prevent the trivalent chromium from being converted to hexavalent chromium as the temperature rises.
[0036] In some embodiments, the raw materials for its preparation include the following components in percentage by weight:
[0037] Magnesia-chrome sand 5%~15%, magnesia-chrome low iron sand 55%~67%, fused magnesia sand 7%~13%, baltic chrome concentrate 9%~13%, baltic chrome lump 1%~4%, aluminum nitride 1%~5%, nickel oxide 0.1%~0.6%, chromium oxide 0.5%~3%, resin powder 0~0.5%, citric acid 0~2%; dextrin 1%~4%, water 1%~2%; the mass percentage of resin powder is not 0. Within the above mass percentage range, the comprehensive performance of semi-recombined magnesia-chrome bricks for copper smelting furnaces, such as high temperature strength performance, slag resistance performance, thermal shock resistance performance, etc., can be made better.
[0038] In some embodiments, the raw materials for its preparation include the following components in percentage by weight:
[0039] Magnesia-chrome sand 5%~10%, magnesia-chrome low iron sand 60%~65%, fused magnesia sand 8%~12%, baltichrome concentrate 10.4%~12%, baltichrome lump 2%~3%, aluminum nitride 2%~3%, nickel oxide 0.3%~0.6%, chromium oxide 1%~1.5%, resin powder 0.2%~0.3%, citric acid 0.5%~1.2%; dextrin 2%~3%, water 1.4%; the mass percentage of resin powder is not 0. Within the above mass percentage range, the comprehensive properties of semi-recombined magnesia-chrome bricks for copper smelting furnaces such as high temperature strength, slag resistance, and thermal shock resistance can be improved.
[0040] Among them, Pakistani chrome concentrate and Pakistani chrome lump both refer to Pakistani chrome concentrate, and the difference between the two is the particle size.
[0041] In some embodiments, in the balochrome concentrate or balochrome lump, Cr2O3≥56wt%, Fe2O3≤15wt%, MgO≤14wt%, Al2O3≤11wt%, SiO2≤1.5wt%, and CaO≤0.59 wt%.
[0042] In some embodiments, in the magnesia-chrome sand, MgO≥48wt%, Cr2O3≥30wt%, Fe2O3≤12wt%, Al2O3≤6.8wt%, CaO≤1.3 wt%, and SiO2≤1.2wt%.
[0043] In some embodiments, in the magnesium-chromium low-iron sand, MgO≥76wt%, Cr2O3≥20.43wt%, Fe2O3≤9.13wt%, Al2O3≤5.34wt%, CaO≤1.36wt%, and SiO2≤0.81wt%.
[0044] In some embodiments, in the fused magnesia, MgO≥97.21wt%, CaO≤1.13wt%, SiO2≤0.84wt%, Fe2O3≤0.59wt%, and Al2O3≤0.17wt%.
[0045] In some embodiments, the mass ratio of balochrome concentrate to aluminum nitride is 1.9~9.2:1. Balochrome concentrate, aluminum nitride, and fused magnesia are mixed and ground in advance. The aluminum oxide contained in the balochrome concentrate can react with aluminum nitride and fused magnesia to form magnesium aluminum oxygen nitrogen phase, effectively fix the aluminum oxide, and prevent the aluminum oxide from reacting with slag. To effectively fix the aluminum oxide in the balochrome concentrate, an appropriate amount of aluminum nitride is required. If the amount of aluminum nitride is too small, the aluminum oxide cannot be effectively fixed, and the slag resistance of the magnesia-chrome brick is insufficient. If the amount of aluminum nitride is too large, the amount of new phases will be too large, resulting in product expansion and cracking. Within the above mass ratio range, the high temperature strength performance, slag resistance, thermal shock resistance and other comprehensive performance of semi-recombined magnesia-chrome bricks for copper smelting furnaces can be made better. Further preferably, the mass ratio of balochrome concentrate to aluminum nitride is 3.4~6:1.
[0046] In some embodiments, the mass ratio of the total mass of the balochrome concentrate and the balochrome lump to the mass ratio of nickel oxide is 22 to 66: 1. Since nickel oxide can react with iron oxide in the chromite to generate nickel-iron spinel liquid phase, promote the reaction of magnesium and chromium to generate magnesia-chrome spinel, and can also react with chromium oxide in the chromite to generate iron-chrome spinel, if the amount of nickel oxide added is too little, it may not be possible to generate a sufficient amount of nickel-iron spinel liquid phase, and the promotion effect on the formation of magnesia-chrome spinel is small. Therefore, it is necessary to regulate the mass ratio of the total mass of the balochrome concentrate and the balochrome lump to the mass ratio of nickel oxide. When the above mass ratio is adopted, the comprehensive performance of the semi-recombined magnesia-chrome bricks for copper smelting furnaces, such as high temperature strength performance, slag resistance, thermal shock resistance, etc., can be made better.
[0047] In some embodiments, the mass ratio of the total mass of the balchrome concentrate and the balchrome lump to the mass ratio of chromium oxide is 4.2 to 26.4:1. The balchrome concentrate, the balchrome lump and the chromium oxide can all be used as raw materials for magnesia-chrome spinel to provide chromium oxide for it. The chromium oxide has a higher purity than chromium ore, and its reaction with magnesia-chrome sand and magnesia sand is more complete, and more magnesia-chrome spinel can be generated. Its chromium oxide is a micro powder, which can fill pores and improve the strength of magnesia-chrome bricks, but chromium oxide is expensive. The higher the amount of chromium oxide added, the higher the strength of the magnesia-chrome brick, the higher the price, but the thermal shock stability is reduced, the molding is difficult, and it is easy to produce layer cracking. The addition of an appropriate amount of chromium oxide can improve the comprehensive performance of magnesia-chrome bricks. When the above mass ratio is adopted, the comprehensive performance of semi-recombined magnesia-chrome bricks for copper smelting furnaces, such as high temperature strength performance, slag resistance, and thermal shock resistance, is better.
[0048] In some embodiments, the magnesia-chrome sand includes magnesia-chrome sand with a particle size of >3 mm and ≤5 mm, magnesia-chrome sand with a particle size of >1 mm and ≤3 mm, magnesia-chrome sand with a particle size of >0 mm and ≤1 mm, and magnesia-chrome sand with a particle size of 200 mesh; the mass ratio of magnesia-chrome sand with a particle size of >3 mm and ≤5 mm, magnesia-chrome sand with a particle size of >1 mm and ≤3 mm, magnesia-chrome sand with a particle size of >0 mm and ≤1 mm, and magnesia-chrome sand with a particle size of 200 mesh is 2~3:4~6:4~5:1.
[0049] In some embodiments, the magnesia-chromium low-iron sand includes magnesia-chromium low-iron sand with a particle size of >3mm and ≤5mm, magnesia-chromium low-iron sand with a particle size of >1mm and ≤3mm, and magnesia-chromium low-iron sand with a particle size of >0mm and ≤1mm; the mass ratio of magnesia-chromium low-iron sand with a particle size of >3mm and ≤5mm, magnesia-chromium low-iron sand with a particle size of >1mm and ≤3mm, and magnesia-chromium low-iron sand with a particle size of >0mm and ≤1mm is 0~1:0~1:0~1.
[0050] In some embodiments, the particle size of the balchrome concentrate is 200 mesh; the particle size of the balchrome lump ore is >0 mm and ≤5 mm.
[0051] In some embodiments, the particle size of the fused magnesia is 200 mesh.
[0052] A second aspect of an embodiment of the present invention provides a method for preparing the semi-rebonded magnesia-chrome brick for a copper smelting furnace, comprising the following steps:
[0053] S1. The aluminum nitride, chrome concentrate, fused magnesia are mixed and co-grinded to obtain a co-grinded powder;
[0054] S2. The co-ground powder is mixed with magnesia-chrome sand, magnesia-chrome low-iron sand, Pakistani chrome lump ore, nickel oxide, chromium oxide, and resin powder to obtain an initial mixture;
[0055] S3. Add dextrin and water to the initial mixture and mix to obtain a mixture;
[0056] S4. forming and firing the mixture to obtain the semi-rebonded magnesia-chrome brick for the copper smelting furnace.
[0057] The preparation method of the semi-rebonded magnesia-chrome brick for the copper smelting furnace of the embodiment of the present invention adopts the method of first mixing and grinding aluminum nitride, ballast chrome concentrate and fused magnesia sand, so that the three are mixed more evenly, so as to react at a firing temperature of about 1780°C to generate magnesium aluminum oxide nitrogen, fix the aluminum oxide in the chromium ore, and improve the slag resistance of the magnesia-chrome brick.
[0058] Preferably, the firing specifically includes the following steps: firing the formed mixture in a firing kiln at a firing temperature of 1800-1820°C, with a cart speed of 120 minutes per cart, and keeping the firing section warm for 6 hours; there should be no pulp-combined products in the first 8 carts and the last 8 carts in the firing kiln. Since pulp products contain alkali metal ions, which will oxidize trivalent chromium into hexavalent chromium, the raw materials need to be isolated from the pulp products to avoid contact.
[0059] In the following embodiments, in the baltic chrome concentrate and baltic chrome lump, Cr2O3≥56wt%, Fe2O3≤15wt%, MgO≤14wt%, Al2O3≤11wt%, SiO2≤1.5wt%, CaO≤0.59 wt%. In the magnesia-chrome sand, MgO≥48wt%, Cr2O3≥30wt%, Fe2O3≤12wt%, Al2O3≤6.8wt%, CaO≤1.3 wt%, SiO2≤1.2wt%. In the magnesia-chrome low-iron sand, MgO≥76wt%, Cr2O3≥20.43wt%, Fe2O3≤9.13wt%, Al2O3≤5.34wt%, CaO≤1.36wt%, SiO2≤0.81wt%. In the fused magnesia, MgO≥97.21wt%, CaO≤1.13wt%, SiO2≤0.84wt%, Fe2O3≤0.59wt%, and Al2O3≤0.17wt%.
[0060] Example 1
[0061] The semi-rebonded magnesia-chrome brick for copper smelting furnace described in this embodiment comprises the following components in percentage by mass:
[0062] 10% magnesia-chrome sand with a particle size of >3mm and ≤5mm, 30% magnesia-chrome sand with a particle size of >1mm and ≤3mm, 25% magnesia-chrome sand with a particle size of >0mm and ≤1mm, 5% magnesia-chrome sand with a particle size of 200 mesh, 3% magnesia-chrome low-iron sand with a particle size of >3mm and ≤5mm, 5% fused magnesia with a particle size of 200 mesh, 15% bachrome concentrate with a particle size of 200 mesh, 0.5% bachrome lump ore with a particle size of >0mm and ≤5mm, 0.5% aluminum nitride, 1% nickel oxide, 4% chromium oxide, 0.8% resin powder, 0.2% citric acid; 2.5% dextrin and 1.4% water were added.
[0063] The method for preparing the semi-rebonded magnesia-chrome brick for the copper smelting furnace of this embodiment comprises the following steps:
[0064] S1. The aluminum nitride, chrome concentrate and fused magnesia were mixed and co-grinded for 25 min to obtain a co-grinded powder;
[0065] S2. The co-ground powder was mixed with magnesia-chrome sand, magnesia-chrome low iron sand, Pakistani chrome lump ore, nickel oxide, chromium oxide, resin powder and stirred for 5 min to obtain an initial mixture;
[0066] S3. Add dextrin and water to the initial mixture, mix, and stir for 25 minutes to obtain a mixture;
[0067] S4. The mixture is formed by a 1600-ton electric screw press into a molding size of 230mm×114mm×75mm, dried in a drying kiln for 24 hours, and then fired in a firing kiln. The firing temperature is 1800°C, the pushing speed is 120 minutes per car, and the firing section is kept warm for 6 hours. There should be no pulp-bonded products in the first 8 cars and the last 8 cars in the firing kiln, and the semi-rebonded magnesia-chrome bricks for the copper smelting furnace are obtained.
[0068] Example 2
[0069] The semi-rebonded magnesia-chrome brick for copper smelting furnace described in this embodiment comprises the following components in percentage by mass:
[0070] 10% magnesia-chrome sand with a particle size of >3mm and ≤5mm, 20% magnesia-chrome sand with a particle size of >1mm and ≤3mm, 20% magnesia-chrome sand with a particle size of >0mm and ≤1mm, 5% magnesia-chrome sand with a particle size of 200 mesh, 5% magnesia-chrome low-iron sand with a particle size of >3mm and ≤5mm, 5% magnesia-chrome low-iron sand with a particle size of >1mm and ≤3mm, 5% magnesia-chrome low-iron sand with a particle size of >0mm and ≤1mm, 13% fused magnesia sand with a particle size of 200 mesh, 9.2% bachrome concentrate with a particle size of 200 mesh, 4% bachrome lump ore with a particle size of >0mm and ≤5mm, 1% aluminum nitride, 0.2% nickel oxide, 0.5% chromium oxide, 0.1% resin powder, 2% citric acid; 2.5% dextrin and 1.4% water were added.
[0071] The preparation method of the semi-rebonded magnesia-chrome brick for the copper smelting furnace in this embodiment is the same as that in Example 1.
[0072] Example 3
[0073] The semi-rebonded magnesia-chrome brick for copper smelting furnace described in this embodiment comprises the following components in percentage by mass:
[0074] 15% of magnesia-chrome sand with particle size >3mm and ≤5mm, 20% of magnesia-chrome sand with particle size >1mm and ≤3mm, 20% of magnesia-chrome sand with particle size >0mm and ≤1mm, 5% of magnesia-chrome sand with particle size >1mm and ≤3mm, 5% of magnesia-chrome low-iron sand with particle size >0mm and ≤1mm, 12% of fused magnesia sand with particle size >200mesh, 11% of bachrome concentrate with particle size >200mesh, 3% of bachrome lump ore with particle size >0mm and ≤5mm, 2% of aluminum nitride, 0.3% of nickel oxide, 1% of chromium oxide, 0.2% of resin powder, 0.5% of citric acid; 2.5% of dextrin and 1.4% of water were added.
[0075] The preparation method of the semi-rebonded magnesia-chrome brick for the copper smelting furnace in this embodiment is the same as that in Example 1.
[0076] Example 4
[0077] The semi-rebonded magnesia-chrome brick for copper smelting furnace described in this embodiment comprises the following components in percentage by mass:
[0078] 10% magnesia-chrome sand with a particle size of >3mm and ≤5mm, 23% magnesia-chrome sand with a particle size of >1mm and ≤3mm, 25% magnesia-chrome sand with a particle size of >0mm and ≤1mm, 5% magnesia-chrome sand with a particle size of 200 mesh, 5% magnesia-chrome low-iron sand with a particle size of >3mm and ≤5mm, 5% magnesia-chrome low-iron sand with a particle size of >0mm and ≤1mm, 8% fused magnesia sand with a particle size of 200 mesh, 12% bachrome concentrate with a particle size of 200 mesh, 2% bachrome lump ore with a particle size of >0mm and ≤5mm, 2% aluminum nitride, 0.3% nickel oxide, 1.4% chromium oxide, 0.3% resin powder, 1% citric acid; 2.5% dextrin and 1.4% water were added.
[0079] The preparation method of the semi-rebonded magnesia-chrome brick for the copper smelting furnace in this embodiment is the same as that in Example 1.
[0080] Example 5
[0081] The semi-rebonded magnesia-chrome brick for copper smelting furnace described in this embodiment comprises the following components in percentage by mass:
[0082] 15% of magnesia-chrome sand with a particle size of >3mm and ≤5mm, 25% of magnesia-chrome sand with a particle size of >1mm and ≤3mm, 20% of magnesia-chrome sand with a particle size of >0mm and ≤1mm, 5% of magnesia-chrome sand with a particle size of 200 mesh, 5% of magnesia-chrome low-iron sand with a particle size of >0mm and ≤1mm, 10% of fused magnesia with a particle size of 200 mesh, 10.4% of bachrome concentrate with a particle size of 200 mesh, 3% of bachrome lump ore with a particle size of >0mm and ≤5mm, 3% of aluminum nitride, 0.6% of nickel oxide, 1.5% of chromium oxide, 0.3% of resin powder, and 1.2% of citric acid; 2.5% of dextrin and 1.4% of water were added.
[0083] The preparation method of the semi-rebonded magnesia-chrome brick for the copper smelting furnace in this embodiment is the same as that in Example 1.
[0084] Example 6
[0085] The semi-rebonded magnesia-chrome brick for copper smelting furnace described in this embodiment comprises the following components in percentage by mass:
[0086] 10% magnesia-chrome sand with a particle size of >3mm and ≤5mm, 27% magnesia-chrome sand with a particle size of >1mm and ≤3mm, 25% magnesia-chrome sand with a particle size of >0mm and ≤1mm, 5% magnesia-chrome sand with a particle size of 200 mesh, 5% magnesia-chrome low-iron sand with a particle size of >3mm and ≤5mm, 8% fused magnesia with a particle size of 200 mesh, 13% bachrome concentrate with a particle size of 200 mesh, 1% bachrome lump ore with a particle size of >0mm and ≤5mm, 3% aluminum nitride, 0.4% nickel oxide, 2% chromium oxide, 0.3% resin powder, 0.3% citric acid; 2.5% dextrin and 1.4% water were added.
[0087] The preparation method of the semi-rebonded magnesia-chrome brick for the copper smelting furnace in this embodiment is the same as that in Example 1.
[0088] Example 7
[0089] The semi-rebonded magnesia-chrome brick for copper smelting furnace described in this embodiment comprises the following components in percentage by mass:
[0090] 15% of magnesia-chrome sand with a particle size of >3mm and ≤5mm, 21% of magnesia-chrome sand with a particle size of >1mm and ≤3mm, 25% of magnesia-chrome sand with a particle size of >0mm and ≤1mm, 5% of magnesia-chrome sand with a particle size of 200 mesh, 5% of magnesia-chrome low-iron sand with a particle size of >1mm and ≤3mm, 7% of fused magnesia with a particle size of 200 mesh, 9.8% of bachrome concentrate with a particle size of 200 mesh, 3% of bachrome lump ore with a particle size of >0mm and ≤5mm, 5% of aluminum nitride, 0.5% of nickel oxide, 3% of chromium oxide, 0.5% of resin powder, and 0.2% of citric acid; 2.5% of dextrin and 1.4% of water were added.
[0091] The preparation method of the semi-rebonded magnesia-chrome brick for the copper smelting furnace in this embodiment is the same as that in Example 1.
[0092] Example 8
[0093] The semi-rebonded magnesia-chrome brick for copper smelting furnace described in this embodiment comprises the following components in percentage by mass:
[0094] 10% magnesia-chrome sand with a particle size of >3mm and ≤5mm, 20% magnesia-chrome sand with a particle size of >1mm and ≤3mm, 20% magnesia-chrome sand with a particle size of >0mm and ≤1mm, 1% magnesia-chrome sand with a particle size of 200 mesh, 5% magnesia-chrome low-iron sand with a particle size of >3mm and ≤5mm, 5% magnesia-chrome low-iron sand with a particle size of >1mm and ≤3mm, 7% magnesia-chrome low-iron sand with a particle size of >0mm and ≤1mm, 14% fused magnesia sand with a particle size of 200 mesh, 5% bachrome concentrate with a particle size of 200 mesh, 4% bachrome lump ore with a particle size of >0mm and ≤5mm, 6% aluminum nitride, 0.1% nickel oxide, 0.1% chromium oxide, 0.1% resin powder, 2.7% citric acid; 2.5% dextrin and 1.4% water were added.
[0095] The preparation method of the semi-rebonded magnesia-chrome brick for the copper smelting furnace in this embodiment is the same as that in Example 1.
[0096] Example 9
[0097] The semi-recombined magnesia-chrome bricks for copper smelting furnaces described in this embodiment have the same mass percentages of other components of the raw materials as those in Example 4, and the same preparation method as that in Example 4, except that the ballast chrome concentrate is 9.2% and the aluminum nitride is 4.8%. That is, the mass ratio of the ballast chrome concentrate to the aluminum nitride is 1.9:1.
[0098] Example 10
[0099] The semi-recombined magnesia-chrome bricks for copper smelting furnaces described in this embodiment have the same mass percentages of other components of the raw materials as those in Example 4, and the same preparation method as that in Example 4, except that the chromite concentrate is 12.6% and the aluminum nitride is 1.4%. That is, the mass ratio of the chromite concentrate to the aluminum nitride is 9:1.
[0100] Embodiment 11
[0101] The semi-recombined magnesia-chrome bricks for copper smelting furnaces described in this embodiment have the same mass percentages of other components of the raw materials as those in Example 4, and the same preparation method as that in Example 4, except that the chromite concentrate is 8% and the aluminum nitride is 6%. That is, the mass ratio of the chromite concentrate to the aluminum nitride is 1.33:1.
[0102] Example 12
[0103] The semi-recombined magnesia-chrome bricks for copper smelting furnaces described in this embodiment have the same mass percentages of other components of the raw materials as those in Example 4, and the same preparation method as that in Example 4, except that the chromite concentrate is 13.5% and the aluminum nitride is 0.5%. That is, the mass ratio of the chromite concentrate to the aluminum nitride is 27:1.
[0104] Example 13
[0105] The semi-recombined magnesia-chrome brick for copper smelting furnace described in this embodiment has the same mass percentage of other components of the raw materials as in Example 4, and the same preparation method as in Example 4, except that the balochrome concentrate is 11.7%, the balochrome lump is 2%, and the nickel oxide is 0.6%. The mass ratio of the total mass of the balochrome concentrate and the balochrome lump to the nickel oxide is 22.8:1.
[0106] Embodiment 14
[0107] The semi-recombined magnesia-chrome brick for copper smelting furnace described in this embodiment has the same mass percentage of other components of the raw materials as in Example 4, and the same preparation method as in Example 4, except that the balochrome concentrate is 12%, the balochrome lump is 2.18%, and the nickel oxide is 0.22%. The mass ratio of the total mass of the balochrome concentrate and the balochrome lump to the nickel oxide is 64.5:1.
[0108] Embodiment 15
[0109] The semi-recombined magnesia-chrome brick for copper smelting furnace described in this embodiment has the same mass percentage of other components of raw materials as in Example 4, and the same preparation method as in Example 4, except that the balochrome concentrate is 11.5%, the balochrome lump is 2%, and the nickel oxide is 0.8%. The mass ratio of the total mass of the balochrome concentrate and the balochrome lump to the nickel oxide is 16.9:1.
[0110] Example 16
[0111] The semi-recombined magnesia-chrome brick for copper smelting furnace described in this embodiment has the same mass percentage of other components of the raw materials as in Example 4, and the same preparation method as in Example 4, except that the balochrome concentrate is 12.2%, the balochrome lump is 2%, and the nickel oxide is 0.1%. The mass ratio of the total mass of the balochrome concentrate and the balochrome lump to the nickel oxide is 142:1.
[0112] Embodiment 17
[0113] The semi-recombined magnesia-chrome brick for copper smelting furnace described in this embodiment has the same mass percentage of other components of raw materials as in Example 4, and the same preparation method as in Example 4, except that the balochrome concentrate is 11%, the balochrome lump is 1.4%, and the chromium oxide is 2.9%. The mass ratio of the total mass of the balochrome concentrate and the balochrome lump to the chromium oxide is 4.3:1.
[0114] Embodiment 18
[0115] The semi-recombined magnesia-chrome brick for copper smelting furnace described in this embodiment has the same mass percentage of other components of raw materials as in Example 4, and the same preparation method as in Example 4, except that the balochrome concentrate is 12%, the balochrome lump is 2.8%, and the chromium oxide is 0.6%. The mass ratio of the total mass of the balochrome concentrate and the balochrome lump to the chromium oxide is 24.7:1.
[0116] Embodiment 19
[0117] The semi-recombined magnesia-chrome brick for copper smelting furnace described in this embodiment has the same mass percentage of other components of raw materials as in Example 4, and the same preparation method as in Example 4, except that the balochrome concentrate is 11%, the balochrome lump is 1%, and the chromium oxide is 3.4%. The mass ratio of the total mass of the balochrome concentrate and the balochrome lump to the chromium oxide is 3.5:1.
[0118] Embodiment 20
[0119] The semi-recombined magnesia-chrome brick for copper smelting furnace described in this embodiment has the same mass percentage of other components of raw materials as that of Example 4, and the same preparation method as that of Example 4, except that the ballast chrome concentrate is 12%, the ballast chrome lump is 3%, and the chromium oxide is 0.4%. The mass ratio of the total mass of the ballast chrome concentrate and the ballast chrome lump to the chromium oxide is 37.5:1.
[0120] Embodiment 21
[0121] The semi-rebonded magnesia-chrome bricks for copper smelting furnace described in this embodiment have the same mass percentages of other components of the raw materials as those in Example 4, and the same preparation method as that in Example 4, except that the resin powder is 1% and the magnesia-chrome sand with a particle size of 200 mesh is 7.3%.
[0122] Comparative Example 1
[0123] The copper smelting furnace of this comparative example uses semi-rebonded magnesia-chrome bricks, and the remaining components and relative contents of the raw materials are the same as those in Example 4, except that aluminum nitride is not added.
[0124] Comparative Example 2
[0125] The copper smelting furnace of this comparative example uses semi-recombined magnesia-chrome bricks, and the remaining components and relative contents of the raw materials are the same as those of Example 4, except that nickel oxide is not added.
[0126] Comparative Example 3
[0127] The copper smelting furnace of this comparative example uses semi-recombined magnesia-chrome bricks, and the remaining components and relative contents of the raw materials are the same as those of Example 4, except that chromium oxide is not added.
[0128] Comparative Example 4
[0129] The copper smelting furnace of this comparative example uses semi-rebonded magnesia-chrome bricks, and the remaining components and relative contents of the raw materials are the same as those in Example 4, except that no resin powder is added.
[0130] The bulk density, porosity and compressive strength of the semi-rebonded magnesia-chrome bricks for copper smelting furnaces obtained in the above embodiments and comparative examples were measured, and the brick inspection and sample preparation were carried out according to GB / T7321. The thermal shock stability was measured by heating the brick to 1000°C, then cooling it in water, then heating it to 1000°C again, then cooling it in water, repeating the process, and recording the number of cracks that appeared after repeated attempts. The test results are shown in Table 1 below.
[0131] The oxygen-enriched side-blown slag of a large domestic copper plant was selected for slag resistance experiment, and the slag composition is shown in Table 2. The slag resistance performance test method is to make the brick into a rectangle of 70×70×70mm, then drill a hole with a diameter of about 35mm and a depth of about 40mm in the middle, then put 50-100g of slag in the hole, put the brick in the furnace and burn it at 1500℃ for 3 hours, then take it out and cut it open to measure the erosion depth. The slag resistance performance test results are shown in Table 3.
[0132] It can be seen from the data in Tables 1 and 3 below that the magnesia-chrome brick of Comparative Example 1, without the addition of aluminum nitride, has poor slag resistance, the magnesia-chrome bricks of Comparative Examples 2 and 3, without the addition of nickel oxide and chromium oxide, have poor high-temperature strength and thermal shock stability, and the magnesia-chrome brick of Comparative Example 4, without the addition of resin powder, has poor high-temperature strength and thermal shock stability. Compared with the comparative examples, the magnesia-chrome bricks of each embodiment of the present invention have better high-temperature strength, thermal shock stability and slag resistance.
[0133] In each embodiment of the present invention, in Embodiments 1-8, the mass percentages of the components of the raw materials are different, wherein the mass percentages of the components in Embodiments 2-7 are within a preferred range compared to Embodiments 1 and 8, and the comprehensive performance of the magnesia-chrome bricks in Embodiments 3-5 is better than that in Embodiments 2, 6, and 7, and the mass percentages of the components are within a further preferred range.
[0134] Compared with Example 4, Examples 9-12 differ in that the mass ratio of balchrome concentrate to aluminum nitride is different. Among them, the mass ratios in Examples 4, 9, and 10 are all within the preferred range, and compared with Examples 11 and 12, the magnesia-chrome bricks have better slag resistance and comprehensive performance.
[0135] Compared with Example 4, Examples 13-16 differ in that the mass ratio of the total mass of the bachrome concentrate and the bachrome lump ore to nickel oxide is different, wherein the above mass ratios in Examples 4, 13, and 14 are all within the preferred range, and compared with Examples 15 and 16, the comprehensive performance of the magnesia-chrome bricks is better.
[0136] Compared with Example 4, Examples 17-20 differ in that the total mass ratio of the chrome concentrate and the chrome lump to the mass ratio of chromium oxide is different. Among them, the mass ratios in Examples 4, 17, and 18 are all within the preferred range, and the comprehensive performance of the magnesia-chrome bricks is better.
[0137] Compared with Example 4, the mass fraction of resin powder in Example 21 is not within the preferred range, and its high temperature strength performance, thermal shock stability, etc. are not as good as those in Example 4.
[0138] Table 1
[0139] <![CDATA[Bulk density after firing / g / cm 3 > Porosity after firing / % Compressive strength after burning / MPa 1400*0.5h high temperature flexural strength / MPa Water cooling thermal shock times Example 1 3.32 13.8 75.6 7.6 7 Example 2 3.32 13.6 82.1 9.2 8 Example 3 3.34 13.3 87.7 11.5 10 Example 4 3.35 13.2 90.5 12.1 10 Example 5 3.34 13.3 86.4 11.2 10 Example 6 3.32 13.6 81.9 9.5 8 Example 7 3.32 13.8 80.3 9.1 9 Example 8 3.32 14 72.3 7.8 7 Example 9 3.35 13.2 89.2 11.9 10 Example 10 3.35 13.3 88.1 11.7 10 Embodiment 11 3.35 13.2 82.3 9.8 9 Example 12 3.35 13.4 84.3 8.9 9 Embodiment 13 3.34 13.2 88.5 11.4 10 Embodiment 14 3.35 13.2 87.2 11.7 10 Embodiment 15 3.34 13.3 80.6 10.1 8 Example 16 3.34 13.5 83.2 9.3 9 Embodiment 17 3.35 13.2 89.2 11.2 10 Embodiment 18 3.35 13.2 87.3 11.6 10 Embodiment 19 3.35 13.3 79.2 9.8 9 Embodiment 20 3.34 13.6 81.4 10.1 8 Embodiment 21 3.30 13.1 78.2 8.9 8 Comparative Example 1 3.35 13.3 85.3 7.2 6 Comparative Example 2 3.35 13.4 64.3 6.5 7 Comparative Example 3 3.34 13.3 67.3 6.8 6 Comparative Example 4 3.38 14 64.7 7.1 6
[0140] Table 2
[0141] Cu (%) Fe (%) S(%) <![CDATA[SiO2(%)]]> CaO (%) <![CDATA[Al2O3(%)]]> MgO (%) Pb (%) Zn(%) 2.17 44.73 0.37 24.12 2.44 4.8 1.17 0.41 1.52
[0142] Table 3
[0143] Left right end Example 1 1.5mm 1mm 1.5mm Example 2 1mm 1mm Not obvious Example 3 Not obvious Not obvious Not obvious Example 4 Not obvious Not obvious Not obvious Example 5 Not obvious Not obvious Not obvious Example 6 1.5mm 1mm Not obvious Example 7 Not obvious 1 mm 1mm Example 8 1mm 1.5mm 1.5mm Example 9 Not obvious Not obvious Not obvious Example 10 Not obvious Not obvious Not obvious Embodiment 11 Not obvious 1mm Not obvious Example 12 1.5 mm 1mm Not obvious Embodiment 13 Not obvious 1mm 1.5 mm Embodiment 14 Not obvious Not obvious Not obvious Embodiment 15 Not obvious 1.5mm Not obvious Example 16 1.5mm Not obvious Not obvious Embodiment 17 Not obvious Not obvious Not obvious Embodiment 18 Not obvious Not obvious Not obvious Embodiment 19 Not obvious Not obvious 1 mm Embodiment 20 Not obvious 1 mm Not obvious Embodiment 21 Not obvious 1 mm Not obvious Comparative Example 1 2mm 1.5mm 2mm Comparative Example 2 1.5mm 1 mm 1.5mm Comparative Example 3 1 mm 1.5mm 1.5mm Comparative Example 4 1 mm 1 mm 1 mm
[0144] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A semi-recombined magnesia-chrome brick for copper smelting furnace, It is characterized in that The raw materials for its preparation include the following components in percentage by mass: 5%~15% of magnesia-chrome sand, 55%~67% of magnesia-chrome low-iron sand, 7%~13% of fused magnesia sand, 9%~13% of bachrome concentrate, 1%~4% of bachrome lump ore, 1%~5% of aluminum nitride, 0.1%~0.6% of nickel oxide, 0.5%~3% of chromium oxide, 0~0.5% of resin powder, and 0~2% of citric acid; 1%~4% of dextrin and 1%~2% of water were added; the mass percentage of citric acid and resin powder was not 0; the mass ratio of bachrome concentrate to aluminum nitride was 1.9~9.2:1; the mass ratio of the total mass of bachrome concentrate and bachrome lump ore to nickel oxide was 22~66:
1.
2. The semi-rebonded magnesia-chrome brick for copper smelting furnace according to claim 1, It is characterized in that The raw materials for its preparation include the following components in percentage by mass: Magnesia-chrome sand 5%~10%, magnesia-chrome low-iron sand 60%~65%, fused magnesia sand 8%~12%, baltichrome concentrate 10.4%~12%, baltichrome lump 2%~3%, aluminum nitride 2%~3%, nickel oxide 0.3%~0.6%, chromium oxide 1%~1.5%, resin powder 0.2%~0.3%, citric acid 0.5%~1.2%; added dextrin 2%~3%, water 1.4%; the mass percentage of citric acid and resin powder is not 0.
3. The semi-rebonded magnesia-chrome brick for copper smelting furnace according to claim 1, Features: In the chromium concentrate and chromium lump, Cr 2 O 3 ≥56wt%Fe 2 O 3 ≤15wt%,MgO≤14wt%,Al 2 O 3 ≤11wt%,SiO 2 ≤1.5wt%, CaO≤0.59 wt%; In the magnesium-chrome sand, MgO≥48wt%, Cr 2 O 3 ≥30wt%Fe 2 O 3 ≤12wt%,Al 2 O 3 ≤6.8wt%, CaO≤1.3wt%, SiO 2 ≤1.2wt%; In the magnesium-chromium low-iron sand, MgO≥76wt%, Cr 2 O 3 ≥20.43wt%,Fe 2 O 3 ≤9.13wt%,Al 2 O 3 ≤5.34wt%, CaO≤1.36wt%, SiO 2 ≤0.81wt%; In the fused magnesia, MgO≥97.21wt%, CaO≤1.13wt%, SiO 2 ≤0.84wt%, Fe 2 O 3 ≤0.59wt%,Al 2 O 3 ≤0.17wt%.
4. The semi-rebonded magnesia-chrome brick for copper smelting furnace according to claim 1, Features: The mass ratio of the total mass of the chromium concentrate and the chromium lump to chromium oxide is 4.2~26.4:
1.
5. The semi-rebonded magnesia-chrome brick for copper smelting furnace according to claim 1, Features: The magnesia-chrome sand includes magnesia-chrome sand with a particle size of >3mm and ≤5mm, magnesia-chrome sand with a particle size of >1mm and ≤3mm, magnesia-chrome sand with a particle size of >0mm and ≤1mm, and magnesia-chrome sand with a particle size of 200 mesh; the mass ratio of magnesia-chrome sand with a particle size of >3mm and ≤5mm, magnesia-chrome sand with a particle size of >1mm and ≤3mm, magnesia-chrome sand with a particle size of >0mm and ≤1mm, and magnesia-chrome sand with a particle size of 200 mesh is 2-3:4-6:4-5:1; The magnesium-chromium low-iron sand includes magnesium-chromium low-iron sand with a particle size of >3mm and ≤5mm, magnesium-chromium low-iron sand with a particle size of >1mm and ≤3mm, and magnesium-chromium low-iron sand with a particle size of >0mm and ≤1mm; the mass ratio of magnesium-chromium low-iron sand with a particle size of >3mm and ≤5mm, magnesium-chromium low-iron sand with a particle size of >1mm and ≤3mm, and magnesium-chromium low-iron sand with a particle size of >0mm and ≤1mm is 0~1:0~1:0~1; The particle size of the balchrome concentrate is 200 mesh; the particle size of the balchrome lump ore is greater than 0 mm and less than or equal to 5 mm; The particle size of the fused magnesia is 200 meshes.
